Perancangan Sistem Informasi Manajemen Ekstrakulikuler di SMAN 4 Kota Bengkulu - Niska Ramadani; Amdhi Yul, Fadlul; Fernanda, Rangga; Wijanarko, Andang (Universitas Putra Indonesia YPTK Padang, 2024)
Extracurricular activities allow students to develop their potential in academic and non-academic fields. Good management and extracurricular activities can be an effective means to develop students' potential as a whole. This study aims to design a system to manage implementation data and evaluate extracurricular activities at SMAN 4 Bengkulu City. The research method used is Research and Development (R&D) by conducting needs analysis, designing new systems, developing prototypes, and trials, and data collection techniques through observation, interviews, and field studies. The performance of the R&D method is a method that can be used to develop a new product or improve existing products. The performance of the R&D method can also produce or develop and enhance products produced in a system to manage extracurricular activities at SMAN 4 Bengkulu City. The results of this study indicate that the management information system developed with the R&D method at SMAN 4 Bengkulu City based on the website has been able to provide convenience in processing extracurricular data. The results of the system's performance can also improve the quality of extracurricular activity management to be more optimal, as well as from data analysis and reporting to support decision-making at SMAN 4 Bengkulu City.